The Effect of Demand Forecasting on Raw Material Inventory Control at CV Wery Group Gunungsitoli - Zalukhu, Dinda Juliyana; Mendrofa, Martha Surya Dinata; Zai, Kurniawan Sarototonafo; Harefa, Idarni (ProBisnis : Jurnal Manajemen, 2025)
This study examines the influence of demand forecasting on raw material inventory control at CV Wery Group Gunungsitoli. The research was motivated by challenges in managing inventory due to fluctuating market demand, which often caused overstocking or stock shortages, leading to inefficiencies in operations. A quantitative research method was employed, with data collected through questionnaires distributed to 30 employees. The data were analyzed using SPSS version 27, including validity and reliability tests, normality and heteroscedasticity tests, simple linear regression, and a T-test. The findings revealed a significant positive relationship between demand forecasting and raw material inventory control, indicated by a regression coefficient of 0.802 with a significance level of 0.000 (p < 0.05). The coefficient of determination (R²) was 0.711, meaning that 71.1% of the variation in inventory control can be explained by demand forecasting. This implies that the more accurate the demand forecasting, the more effective the inventory control. The study suggests that CV Wery Group should improve forecasting capabilities as a strategic tool to enhance operational efficiency and support production continuity.